Dental Pulp - the Source of Mesenchymal Stem Cells - J. Suchánek; T. Soukup; R. Ivančaková; B. Víšek (Czech Dental Chamber, 2008)
Objective: the study aimed to isolation of dental pulp stem cells (DPSC), determination of proliferative and differentiation potential and observation of morphological changes and viability of DPSC cultured in vitro. Methods: the authors used a total of 16 DPSC cell lines isolated from the third molars. The cells were cultured in a modified medium for mesenchymal stem cells (MSC) enriched with growth factors (EGF, PDGF), 2% FCS and ITS supplement. For the determination of quantitative parameters and cell viability the Vi-Cell XR and Z2 Counter were used. Results: Enzyme dissociation of the complete dental pulp provided isolation of 45 ± 6 (10- 108) stem cells. These cells were cultured through 60 population duplications (PD) in a modified medium for MSC. The analysis revealed increased time required for duplication from original 15-23 h for the first PD to 24-35 h for the subsequent 30 PD. Viability of the cultured cells was continually 96 ± 3%. In the course of the long-term cultivation of DPSC no signs of culture degeneration or spontaneous differentiation of the cells were observed. Conclusion: these cells represent a morphologically homogenous population with a marked proliferation potential and stable phenotype in cultivation conditions in vitro. The dental pulp stem cells represent a highly potent source of histocompatible stem cells for cellular therapy, which is not limited to diseases of dental pulp and periodontium only. Their broad differentiation potential opens the way for application of these cells in other medical branches.